Isolated Apophyseal Avulsion of the Greater Trochanter Treated by Minimally Invasive Osteosynthesis: A Case Report - Malerba, G (Malays Orthop J, 2020)
Isolated apophyseal avulsion of the greater trochanter is a rare condition in the paediatric population, frequently related to avascular necrosis of the femoral head. Since there are few cases in the literature, there is no consensus regarding the best treatment of this injury. Our study describes the case of a 9-year-old patient with an avulsion of the right greater trochanter. A minimally invasive osteosynthesis was performed, achieving complete clinical and radiographic healing of the patient and no long-term complications after four years.